Saccadic dysmetria and "intact" smooth pursuit eye movements after bilateral deep cerebellar nuclei lesions. Issue 7 (July 1994) - Büttner, U; Straube, A; Spuler, A
Abstract : Two patients with well defined lesions of midline cerebellar structures including the fastigial nuclei on both sides presented with saccadic hypermetria but well preserved smooth pursuit eye movements. This is a remarkable finding as the oculomotor vermis (lobules VI, VII) and the fastigial nucleus are known to play a part in the control of smooth pursuit eye movements and unilateral fastigial lesions lead to a smooth pursuit deficit to the contralateral side (besides saccadic dysmetria). The results are discussed with regard to related deficits seen in patients with Wallenberg's syndrome and after lesions of the pontine reticular formation.